2014
DOI: 10.2147/idr.s71505
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a unique propolis compound (PropoelixTM) on clinical outcomes in patients with dengue hemorrhagic fever

Abstract: BackgroundDengue fever is a mosquito-borne virus belonging to the family Flaviviridae. It is an old virus that has re-emerged globally over the past 20 years and now causes a global burden of 50 million infections per year across approximately 100 countries. Despite this, there is no safe vaccine available, and therapy is largely supportive. Its pathogenesis is multifaceted and currently still poorly understood, leading to a lack of disease-specific therapy. Propolis is a natural antiviral and anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…CLEC5A has been also implicated in the induction of apoptosis and damage of endothelial cells in a murine model of DENV infection, in which the release of large amounts of TNF-α, as well as IL-6 and MCP-1, conduced to several vascular leakage, organ damage, extensive hemorrhage and death of infected mice 40. A clinical trial showed the relevance of TNF-α measurement as part of the indicators of recovery in patients with severe dengue and thrombocytopenia; indeed, treatment with Propoelix TM induced faster recovery in platelet counts and shorter length of hospitalization that were associated with lower levels of TNF-α in the treated group 52. Additional evidence of the role of TNF-α, IL-6 and other cytokines in dengue immunopathology comes from a study that prevent endothelial lesions in a murine model of dengue by direct blocking with antibodies against each cytokine 13.…”
Section: Discussionmentioning
confidence: 99%
“…CLEC5A has been also implicated in the induction of apoptosis and damage of endothelial cells in a murine model of DENV infection, in which the release of large amounts of TNF-α, as well as IL-6 and MCP-1, conduced to several vascular leakage, organ damage, extensive hemorrhage and death of infected mice 40. A clinical trial showed the relevance of TNF-α measurement as part of the indicators of recovery in patients with severe dengue and thrombocytopenia; indeed, treatment with Propoelix TM induced faster recovery in platelet counts and shorter length of hospitalization that were associated with lower levels of TNF-α in the treated group 52. Additional evidence of the role of TNF-α, IL-6 and other cytokines in dengue immunopathology comes from a study that prevent endothelial lesions in a murine model of dengue by direct blocking with antibodies against each cytokine 13.…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant clinical trial was conducted by Soroy et al [ 225 ] on dengue hemorrhagic fever patients. Their double-blind, randomized and placebo-controlled trial evaluated the propolis product Propoelix TM (two 200 mg capsules, three times a day), demonstrating an improvement in platelet counts and a decrease in TNF-alfa, promoting a reduction in the duration of hospitalization time of the patients.…”
Section: Safety and Efficacy Studiesmentioning
confidence: 99%
“…For preventive purposes, 30 drops/day or one capsule, are usually taken. However, considering the dosage safely used by Soroy et al [ 225 ] of 1200 mg/day, in more severe cases of COVID-19, dosages higher than 500 mg/day could be useful.…”
Section: Safety and Efficacy Studiesmentioning
confidence: 99%
“…Propolis extracts have been tested for many different types of biological and pharmacological activities (Burdock, 1998;Farooqui & Farooqui, 2010;Sforcin & Bankova, 2011), including in clinical trials (Henshaw et al, 2014;Hoheisel, 2001;Paulino, Coutinho, Coutinho, & Scremin, 2014;Soroy, Bagus, Yongkie, & Djoko, 2014;Vaz Coelho et al, 2007). Most significant is the number of clinical trials in dentistry (Anauate-Netto et al, 2014;Pereira et al, 2011;Prabhakar, Karuna, Yavagal, & Deepak, 2015;Purra, Mushtaq, Acharya, & Saraswati, 2014;Torwane et al, 2013).…”
Section: Other Tests Including Clinical Testsmentioning
confidence: 99%